Advancing universal health coverage in the COVID-19 era: An assessment of public health services technical efficiency and applied cost allocation in Cambodia - Robert J. Kolesar; Peter Bogetoft Pedersen; Vanara Chea; Guido Erreygers; Sambo Pheakdey (Health Economics Review, 2022)
Background: Achieving universal health coverage (UHC) is a global priority and a keystone element of the 2030 Sustainable Development Goals. However, COVID-19 is causing serious impacts on tax revenue and many countries are facing constraints to new investment in health. To advance UHC progress, countries can also focus on improving health system technical efficiency to maximize the service outputs given the current health financing levels. Methods: This study assesses Cambodia's public health services technical efficiency, unit costs, and utilization rates to quantify the extent to which current health financing can accommodate the expansion of social health protection coverage. This study employs Data Envelopment Analysis (DEA), truncated regression, and pioneers the application of DEA Aumann-Shapley applied cost allocation to the health sector, enabling unit cost estimation for the major social health insurance payment categories. Results: Overall, for the public health system to be fully efficient output would need to increase by 34 and 73% for hospitals and health centers, respectively. We find public sector service quality, private sector providers, and non-discretionary financing to be statistically significant factors affecting technical efficiency. We estimate there is potential supply-side "service space" to expand population coverage to an additional 4.69 million social health insurance beneficiaries with existing financing if the public health system were fully efficient. Conclusions: Public health service efficiency in Cambodia can be improved by increasing utilization of cost-effective services. This can be achieved by enrolling more beneficiaries into the social health insurance schemes with current supply-side financing levels. Other factors that can lead to increased efficiency are improving health service quality, regulating private sector providers, focusing on discretionary health financing, and incentivizing a referral system.
Keywords: 330; Health service efficiency; Social health protection; Costing; Cost allocation; Universal health coverage; Cambodia